Neural modulation of behavioral state transitions in foraging strategies in C. elegans - Blanco, Maria Gabriela (2023)
Adequate feeding behavior is essential for animal survival and it is regulated not only by the digestive system but also by the nervous system (NS). The NS allows the animal to respond flexibly to changes in the environment depending on the availability of food and the nutritional internal state. Despite feeding behaviors have been studied for decades, understanding the mechanisms involved in different animals´ responses to food depending on its internal state (satiated or fasted/stressed) is still a major challenge. Referred to as the “happiness hormone”, serotonin (5-HT) has been shown to increase with food stimulus and modulate feeding in different animals, suggesting that the role of 5-HT is conserved in nature. On the other hand, noradrenaline (NA), implicated in triggering a stress response, is involved in appetite control by reducing food ingestion. Interestingly, there are reports showing that a lesion of the serotonergic system enhances the effect of noradrenergic drugs. These findings indicate an interaction between serotonergic and noradrenergic signaling. However, the mechanism and relevance of this interplay are not entirely clear. Therefore, our goal is to investigate the molecular processes underlying this interaction. The complexity of the mammalian brain complicates the study of neuronal processes. The nematode Caenorhabditis elegans is suitable for understanding neuronal signaling because of its simple and well-described nervous system. We found that during prolonged fasting, animals decrease their locomotion, which can be resumed by adding tyramine (TA), the analog of NA in invertebrates. 5-HT produces the opposite effect by reducing locomotion, suggesting that 5-HT acts antagonistically to TA. Moreover, it has been shown that when the environment improves and fasted animals encounter food, they release 5-HT to slow their locomotion and promote feeding. Interestingly, we found that this slowing response and the activity of the serotonergic neurons upon food encounter are enhanced in TA-deficient mutants compared to wild-type animals. Given that we also show that TA levels decrease during fasting, we hypothesize that this disinhibits the serotonergic neurons and favors their activity upon refeeding, allowing the animal to exploit the new source of food. Considering the conservation of neuronal components, we believe that our results may contribute to the understanding of the nervous control of state dependent foraging strategies